2017
DOI: 10.3390/toxins9040128
|View full text |Cite
|
Sign up to set email alerts
|

Ostreolysin A/Pleurotolysin B and Equinatoxins: Structure, Function and Pathophysiological Effects of These Pore-Forming Proteins

Abstract: Acidic ostreolysin A/pleurotolysin B (OlyA/PlyB, formerly known as ostreolysin (Oly), and basic 20 kDa equinatoxins (EqTs) are cytolytic proteins isolated from the edible mushroom Pleurotus ostreatus and the sea anemone Actinia equina, respectively. Both toxins, although from different sources, share many similar biological activities: (i) colloid-osmotic shock by forming pores in cellular and artificial membranes enriched in cholesterol and sphingomyelin; (ii) increased vascular endothelial wall permeability … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Pleurotolysin was detected in the Pleurotus species. It is a sphingomyelin-specific cytolysin composed of two subunits (17 and 59 kDa) that integrate to cause an outflow of K ions leading to selective lysis of cancer cells [ 81 , 82 ]. Serine proteinase plays an important role in the antiviral properties of mushrooms [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pleurotolysin was detected in the Pleurotus species. It is a sphingomyelin-specific cytolysin composed of two subunits (17 and 59 kDa) that integrate to cause an outflow of K ions leading to selective lysis of cancer cells [ 81 , 82 ]. Serine proteinase plays an important role in the antiviral properties of mushrooms [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…This protein binds to lipid membranes and forms pores, 25 disrupting cell membrane integrity and causing cells to lyse. 26 The disruption in membrane structure causes cell damage, triggering lipid peroxidation, and increasing oxidative stress, 27 which results in inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, hypoxia refers to any kind of physiological oxygen deficiency or tissue oxygen demand deficiency state and the integration of local responses defines hypoxia as a paradigm of reactions affecting the entire body (86,132,133). Studies have shown that inhibiting the breathing of rats caused obvious cardiotoxicity (79, [134][135][136][137][138].…”
Section: Hypoxiamentioning
confidence: 99%